2016
DOI: 10.4049/jimmunol.1601094
|View full text |Cite
|
Sign up to set email alerts
|

IL-27 Is Essential for Suppression of Experimental Allergic Asthma by the TLR7/8 Agonist R848 (Resiquimod)

Abstract: Different models of experimental allergic asthma have shown that the TLR7/8 agonist resiquimod (R848) is a potential inhibitor of type 2 helper cell–driven inflammatory responses. However, the mechanisms mediating its therapeutic effects are not fully understood. Using a model of experimental allergic asthma, we show that induction of IL-27 by R848 is critical for the observed ameliorative effects. R848 significantly inhibited all hallmarks of experimental allergic asthma, including airway hyperreactivity, eos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 62 publications
2
28
0
Order By: Relevance
“…Serum and BALF IL-17 levels were significantly downregulated in the OVA+IL-27 group compared with those noted in the OVA group. These findings suggested that IL-17 plays a role in allergic asthma and that IL-27 acts in a manner antagonistic to IL-17, which is in accordance with previously reported data (21,53). Moreover, a previous study revealed that high levels of IL-17 were found in induced sputum and bronchial biopsies obtained from severe asthmatics and were associated with poor patient response to steroids (54).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Serum and BALF IL-17 levels were significantly downregulated in the OVA+IL-27 group compared with those noted in the OVA group. These findings suggested that IL-17 plays a role in allergic asthma and that IL-27 acts in a manner antagonistic to IL-17, which is in accordance with previously reported data (21,53). Moreover, a previous study revealed that high levels of IL-17 were found in induced sputum and bronchial biopsies obtained from severe asthmatics and were associated with poor patient response to steroids (54).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, Miyazaki et al (20) reported that IL-27R (-/-) mice challenged with ovalbumin (OVA) exhibited increased asthmatic phenotypes, suggesting IL-27 suppresses airway inflammation, hyperresponsiveness and remodeling via the STAT1 and STAT3 pathways in mice with allergic asthma dEGAN LU 1 , JIAMENG LU 2 , XIAOQING JI 3 , YANBO JI 1 , ZEWEN ZHANG 4 , HAIYING PENG 5 , FEI SUN 5 and CAIQING ZHANG 1 that IL-27 plays a pivotal role in the inhibition of lung inflammation and AHR. Jirmo et al (21) demonstrated that IL-27 is critical for the control of allergic asthma. Therefore, IL-27 is a novel, promising preventative agent for alleviating asthma development and exacerbation.…”
Section: Introductionmentioning
confidence: 99%
“…This agonist for TLR7 and TLR8 is currently used for the development of a drug with similar fields of application as for imiquimod (Spirig Pharma, Egerkingen, Switzerland). In different murine models, R848 was shown to be a potent suppressor of experimentally induced acute asthmatic inflammation and even reversed established asthma by inhibiting T H 2 responses through induction of IFN‐γ and the T H 1‐polarizing cytokine IL‐12 in a TLR8‐dependent manner . The induction of IL‐12 by R848 could also be observed in human moDCs and these cells were primed to induce T H 1 polarization .…”
Section: Allergy and Asthmamentioning
confidence: 98%
“…Another level of complexity is that both mIL‐6R and sIL‐6R also bind the p28 subunit of IL‐27, with the sIL‐6R/p28 complex having antiviral activity . IL‐27 has been implicated in the aetiology of allergic disease, both by functional and genetic association studies . Therefore, a role for IL‐6R inhibition in IL‐27‐dependent allergic responses should also be considered in future studies.…”
Section: Discussionmentioning
confidence: 99%